Zucchini Plants Alter Gene Expression and Emission of (E)-β-Caryophyllene Following Aphis gossypii Infestation - Vitiello, Alessia; Molisso, Donata; Digilio, Maria Cristina; Giorgini, Massimo; Corrado, Giandomenico; Bruce, Toby J. A.; D’Agostino, Nunzio; Rao, Rosa (Frontiers in Plant Science, 2021)
Zucchini (Cucurbita pepo L.) is widely cultivated in temperate regions. One of the major production challenges is the damage caused by Aphis gossypii (Homoptera: Aphididae), a polyphagous aphid, which can negatively affect its host plant, both directly by feeding and indirectly by vectoring viruses. To gain insights into the transcriptome events that occur during the zucchini-aphid interaction and to understand the early-to-late defense response through gene expression profiles, we performed RNA-Seq on zucchini leaves challenged by A. gossypii (24, 48 and 96 hours post-infestation). Data analysis indicated a complex and dynamic pattern of gene expression and a transient transcriptional reconfiguration that involved more than 700 differentially expressed genes, including a large number of defence-related genes. The down-regulation of key-genes of plant immunity, such as LRR protein kinases, transcription factors and genes associated with direct (i.e. protease inhibitors, cysteine peptidases, etc.) and indirect (i.e. terpene synthase) defence responses, suggests the aphid ability to manipulate plant immune responses. We investigated also the emission of volatile organic compounds from infested plants and observed a reduced emission of (E)-β-caryophyllene at 48 hpi, likely the result of aphid effectors, which reflects the down-regulation of two genes involved in the biosynthesis of terpenoids. We showed that (E)-β-caryophyllene emission was modified by the duration of plant infestation and by aphid density and that this molecule highly attracts Aphidius colemani, a parasitic wasp of A. gossypii. With our results, we contributed to the identification of genes involved in cucurbit plant interactions with phloem feeders. Our findings may also help pave the way towards developing tolerant zucchini varieties and to identify molecules for sustainable management of harmful insect populations.